The performance of washing contractors based on the volume of washed denim garments for export - Reyes, Marines G.
The Philippine garments and textile industry which started from cottage type ventures in the late 1940's and 1950's, engaged mainly in dressmaking, tailoring and subcontracting activities for American principals (GTEB "Winning the World, 2000). For the past ten year Philippine garment industry is becoming an internationally preferred source of quality garments. Market increased by the first half of the decade for bottoms like jeans, shorts, and skirts. Atleast two thirds of these, according to Hada's study, are composed of denim which is the primary choice of most American consumers for casual wear (Hada, 1995). Since denim has became a classic clothing every season, buyers all over the world increase their demand especially for trousers. Technological innovations in the washing industry have brought about efficiency and simplicity in production. As innovation occurs market competitiveness moves too fast. Washing contractors need to embrace new technologies in order to gain competitive advantage. Different washing techniques, which make the manufacturing process simpler and easier to handle, were specified in order to achieve the softness, performance, fashionable look and reasonably priced overall quality the buyers want. This study is a documentary survey of the performance of washed denim garments. There were 10 washing contractors selected purposively. Out of then, seven washing contractors responded. The data was gathered through a survey of the problems and the suggested development plans. The interpretation was based on Likert scale. The mean and average mean of the problems and the development plans were used for further analysis in relation to the company's sales performance. A brief description of the respondent firms were also obtained such as the company name, the year it started to wash denim garments for export and their target market. This research present a comparative report of the sales performance for the past 5 years through its volume in kilograms, and the factors affecting the performance of seven washing contractors who belong to the top fifteen washing contractors washing garments for export. Kilograms were the unit used in measuring the volume as it is the standard and constant to the companies' observed. The results of the questionnaire show that washing contractors were affected by lack of raw materials used in the process. In response to this problem, washing contractors agree to increase production by encouraging some developments. They recommend that government agencies like Philippine Textile Research Institute (PTRI) provides assistance through research of new chemicals that can be used without spending more. Aside from the problem identified results of interview and questionnaire survey show that one hundred percent (100%) of the respondent agree that the main problem they encountered was improper distribution of quota/quota allocation of the Garment and Textile Export Board (GTEB). Washing contractors believe that to make a significant change proper management of quota should be done. The washing industry has been there for a very long time. The challenges and threats they encounter have kept them struggling to survive. Global excellence is what they starting to realize amid the growing competition. Finally, the government, manufacturer and washing contractors must share a common vision and be reunited in their efforts in order to achieve growth in garment export. They should work hand in hand because they are all benefited in this field of business. They should implement concrete and measurable objectives because each has a role to play in creating a better garment industry.